A note on the usefulness of skinfold thickness condition score for estimating body fat content in Boran cattle - Nicholson, M.J.; Little, D.A. (Cambridge University Press, 1989)
An attempt was made to use anal skinfold thickness as a quantitative measurment to estimate body fatness in Boran cattle (Bos indicus). Using the normal single-operator technique the relationship between skinfold thickness and the other measurements was poor but was greatly improved by using two operators. It nevertheless remained inferior to body condition score, which was very highly correlated with estimated body fat proportion. It was concluded that condition scoring provides a valuable index of the nutritional status of Bos indicus cattle, and that measurements of anal fold thickness are not applicable to such animals.